Pengaruh Mulsa Biodegradable Polypropylene dan Fungisida Organik terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Sri Astria Amanda Syifa; Nurmayulis Nurmayulis; Endang Sulistyorini; Andree Saylendra (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
This study aimed to determine the effect of using biodegradable polypropylene mulch and organic fungicide doses on the growth and yield of cayenne pepper plants. The research was conducted from 09 December to 02 March 2024 in the Cibungur Village Garden Land, Buniwangi Village, Surade District, Sukabumi Regency, West Java Province. This research used a Split Plot Design, which was arranged based on two treatment factors, factor 1, namely M0= control treatment, M1= polyethylene mulch, and M2= polypropylene mulch. Factor 2 is F0= control treatment, F1= 15 g, F2= 20 g, F3= 25 g, and there are 12 treatment combinations repeated three times, so there are 36 experimental units and consist of 2 plants, so there are 72 plants. The observation parameters were plant height, number of leaves, number of fruit per plant, number of fruit per plot, wet weight of fruit per plant, wet weight of fruit per plot, dry weight of fruit per plant, and dry weight per plot. The use of polypropylene mulch can significantly increase the growth of plant height, number of leaves, number of fruit per plant, number of fruit per plot, wet weight of fruit per plant, wet weight of fruit per plot, dry weight of fruit per plant and dry weight per plot. Giving a dose of 25 g can significantly increase the growth of plant height, number of leaves, number of fruit per plant, number of fruit per plot, wet weight of fruit per plant, wet weight of fruit per plot, and dry weight of fruit per plant. Dry weight per plant and dry weight per plot. There was a real interaction between biodegradable polypropylene mulch and a dose of 25 g organic fungicide on the wet fruit weight per plant and wet fruit weight parameters per plot.